Nigeria bank reference - Olusola, Aminu (Abuja, Nigeria : Precise Concept, 2002)
This book provides information based on the international standard of assessing the health of a bank namely: history of the bank, capital, assert quality, management structure, earnings and liabilities. It contains two to three years audited financial summary of all banks in Nigeria including the varieties of unique banking products and services.
ne 07/09/2021
Ref.
Keywords: Banks and banking; Nigeria